Amlodipine-Induced Subacute Cutaneous Lupus Erythematosus Localized to Non-Sun-Exposed Areas - Takahiro Mizuta; Miyuki Kato (Karger Publishers, 2022)
The cutaneous manifestations of subacute cutaneous lupus erythematosus (SCLE), a subset of cutaneous lupus erythematosus, arise most often in sun-exposed areas. We report a case of SCLE with atypical distribution, following treatment with amlodipine. This highlighted a possible clue that can be used to clinically distinguish a drug-induced case from an idiopathic disorder. A 92-year-old Japanese woman presented with a 2-month history of progressive erythematous, papulosquamous rash, and annular plaques in non-sun-exposed sites with no systemic symptoms. Irbesartan/amlodipine besilate combination tablets were prescribed 8 months earlier for hypertension. The appearance of the skin eruptions, results of immunopathological findings, and temporal relationship between the rash and drugs were suggestive of a diagnosis of drug-induced SCLE, which was confirmed by the spontaneous resolution of these cutaneous eruptions within 4 weeks after cessation of amlodipine treatment. The evaluation of possible associations with medications should be performed in patients presenting with clinical features characterizing SCLE in atypical sites (non-sun-exposed areas).